Institutional resistances before school mediation. An inquiry in the conflict settings - Carrasco Pons, Silvia; Villà Taberner, Rita; Ponferrada Arteaga, Maribel (Revista de Antropología Social, 2016)
This paper deals with the conceptions of the different school actors about the meaning and the implications of mediation in their schools, drawing on data from a qualitative approach carried out as part of a wider project to map mediation perspectives and practices in Catalonia. The authors analyze the scope of the situations regarded as suitable or unsuitable for the introduction of restorative practices, as well as the resistance to change in the practice of conflict resolutions and in the democratization of school culture.